Exploring an ICT-Enabled participative smart city governance system: an Indian context - Dillip Kumar Das (International Journal of Urban Sustainable Development)
This study examines the relationship between Information and Communication Technology (ICT) and smart governance in smart cities, emphasising the importance of participation and responsiveness for effective governance. Focused on India, it evaluates global smart city governance models, comparing them with the Indian system. The study analyses the current governance structure and the potential of ICT to enhance participatory governance in smart cities. Despite challenges, including limited participation and responsiveness, ICT holds promise for improving governance. The study proposes a governance framework based on pluralist democracy, with ICT playing a central role in fostering collaboration among stakeholders. Despite obstacles like the digital divide, this model prioritises people and ICT within India’s governance, offering insights relevant globally to democratic nations. It presents a new conceptualisation for smart city governance, applicable not only to India but also to democracies worldwide.